Galanin receptor 2-neuropeptide Y Y1 receptor interactions in the amygdala lead to increased anxiolytic actions - Narváez-Peláez, Manuel; Millón-Peñuela, Carmelo; Borroto Escuela, Dasiel Óscar; Flores-Burgess, Antonio; Santín-Núñez, Luis Javier; Parrado-Romero, Concepción; Gago-Calderón, Belén; Puigcerver-Martínez, Araceli; Fuxe, Kjell; Narváez-Bueno, José Ángel; Díaz-Cabiale, Zaida (Springer Nature, 2014)
Galanin (GAL) and Neuropeptide Y (NPY) are neuropeptides involved in behaviors associated with anxiety. Both neuropeptides interact in several central functions. However, the potential behavioral and cellular interactions between them in anxiety are unknown. GAL was found to act through GAL receptor 2 (GALR2) to enhance NPYY1 receptor (NPYY1R) mediated anxiolytic behaviors in rats. Using receptor autoradiography, c-fos expression and in situ proximity ligation assay, the medial paracapsular intercalated nuclei of the amygdala were determined to be a key area in the interaction probably involving the formation of GALR2/NPYY1R heteroreceptor complexes. In cell cultures co-stimulation of GALR2 and NPYY1R induced changes in the functions of these receptors. The changes involved a potentiation of the decrease in the phosphorylation of CREB induced by NPYY1R and a delay in the internalization of NPYY1R. These results indicate that GALR2/NPYY1R interactions can provide a novel integrative amygdaloid mechanism in anxiety.
Keywords: Neuropéptidos; Angustia; Depresión mental; Galanin; GALR2; NPY-Y1R; Anxiety